Analisa Usahatani Padi Dengan Sistem Tanam Mesin Rice Transplanter Di Kecamatan Geneng Kabupaten Ngawi (Study Kasus Desa Dempel Kecamatan Geneng Kabupaten Ngawi) - Ratna Mustika Wardhani; Wigik Darsono (Universitas Merdeka Madiun, 2021)
Abstractâ€” Rice is the staple foodstuff in Indonesia, rice consumption in Indonesia has increased every year. The obstacle found in rice production centers is the scarcity of labor, which has become a barrier to rice farming, especially the labor for planting rice seeds. The limited number of workers when planting rice seeds causes the rice planting schedule to not be synchronized. So there needs to be a change in rice farming, one of which is by means of a rice planting system using a rice planting machine, because rice planting machines do not require a lot of labor. Apart from having less labor, the use of rice planting machines also reduces costs. The method used is descriptive, namely research that leads to the disclosure of a problem or situation as it is. The method used is Î = TR-TC (Î = farm profits) TR = total revenue, and TC = total production costs consisting of fixed costs and variable costs. The results showed that the R / C ratio of rice farming with the machine cropping system was feasible to develop with an R / C ratio of 2.25.Â Keywordsâ€”: Farming Analysis; Rice Plants; Rice Transplanter.